The Research on Residential Interior Space Design Based on the Individual Needs for Elderlies - Wang, Feng; Buranaut, Isarachai (Journal of Roi Kaensarn Academi, 2024)
The form of aging in China is severe. In this context, the needs of the older people are becoming more and more prominent. Due to the limitations of the social development level and the influence of traditional concepts, the model of “aging in place” has been widely promoted in China. It is increasingly important to integrate the individual needs of the older people into the interior space design of home care. Age-friendly home care interior space design aims to create a safe, convenient, personalized and intelligent living environment to meet the diverse needs of the older people in their daily lives. This paper firstly proposes four major design principles, namely, the principle of complying with the co-existence of spatial safety and convenience, the principle of co-existence of continuity and flexibility, the principle of personalization in the selection of decorative elements, and the principle of intelligent spatial design, which provide a systematic framework for designers. These principles theoretically build the foundation of age-friendly space design and provide guidelines for actual design. And four major design strategies are proposed based on these four principles. Through these design principles and strategies, this paper provides scientific and reasonable guidance for the design of age-friendly home care interior space, aiming to create a safe, comfortable and personality-filled living environment for older people.